2016
DOI: 10.1155/2016/2918735
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Metallic versus Metallic Solution in Treating Periprosthetic Femoral Fractures: Outcome Assessment

Abstract: Introduction. The periprosthetic fracture of the femur is, in order of frequency, the fourth leading cause (5.9%) of surgical revision. Our study aims to demonstrate how the grafting of bone splint betters the outcomes. Materials. We treated 15 periprosthetic femoral fractures divided into two groups: PS composed of 8 patients treated with plates and splints and PSS involving 7 patients treated only with plates. The evaluation criteria for the two groups during the clinical and radiological follow-up were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Except for plates, bone splints are commonly used. Carta et al [ 30 ] reported that cortical allogenic splints should be considered the use instead of metal plates for the treatment of periprosthetic femoral fracture, which usually has bone loss and/or a potential mechanical instability. In a cadaveric study, Peters et al [ 31 ] concluded that allograft cortical splints offer biomechanical advantages as an alternative to metal plates for the fixation of femur fracture below a well-fixed femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…Except for plates, bone splints are commonly used. Carta et al [ 30 ] reported that cortical allogenic splints should be considered the use instead of metal plates for the treatment of periprosthetic femoral fracture, which usually has bone loss and/or a potential mechanical instability. In a cadaveric study, Peters et al [ 31 ] concluded that allograft cortical splints offer biomechanical advantages as an alternative to metal plates for the fixation of femur fracture below a well-fixed femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…15 According to our modern experience, lateral plate and medial strut allograft is the best choice to treat the perimplants failure 16 and periprosthetic femoral fracture. [16][17][18] The cortical strut only allografts confer stability to the fracture site, and they can incorporate and ultimately increase the femoral bone stock. 19 They also "lengthen" the working length of the screws.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
“…Our studies have suggested that cortical struts predictably unite, remodel, mature and not breakage's risk. [16][17][18][19] To obtain the maximum stability of the metal-biological construct the osteosynthesis with screws should always be used (Figure 1 and Figure 2) because the use of metal cerclage cables can lead to implant failures and subsequent revisions. 22,24 Other authors suggested Total femur replacements or a megaprosthesis are typically reserved for patients with lim-ited bone stock and loose implants or in the situation of multiple failed fracture fixation or persistent fracture nonunion, revision to a megaprosthesis may provide a route to definitive treatment.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
“…Many studies have reported a higher union rate and it is recommended to routinely use cortical strut allograft for the treatment of periprosthetic fractures [ 13 15 ]. However, in recent years, studies have reported that locking plate alone can still achieve high union rate and function [ 16 18 ], and the use of cortical strut allografts also has disadvantages, such as high infection rates, soft tissue stripping and expensive material [ 19 ]. To date, there are only limited comparative studies on cortical strut allograft for Vancouver type B1 and C fracture.…”
Section: Introductionmentioning
confidence: 99%